Adaptation of O157:H7 and non-O157 Escherichia coli strains in orange juice and subsequent resistance to UV-C radiation. (1st March 2022) - Oteiza, Juan M.; Caturla, Magdevis Y.R.; Prado-Silva, Leonardo do; Câmara, Antonio A.; Barril, Patricia A.; Sant'Ana, Anderson S.; Giannuzzi, Leda; Zaritzky, Noemi
Abstract: This study assessed the acid-adaptation of pathogenic and non-pathogenic strains of Escherichia coli in orange juice and the microbial resistance to the subsequent UV-C radiation treatment. Nine Shiga toxin-producing E. coli (STEC) and one strain of a non-pathogenic surrogate E. coli were used in this study. Each E. coli strain was inoculated in orange juice, following pre-exposure during 0, 1, 2, and 3 h at 10 °C. Then, the inoculated juices with the ten different strains separately were exposed to 0 and 2 J/cm 2 of UV-C radiation. The D value (i.e., the UV-C dose in J/cm 2 required to cause a one-log reduction in the target microorganism) was calculated. Further, the resistance coefficient [RC; i.e., the ratio between the D -values for the control condition ( D 0h ) and each pre-exposure tested time ( D 1h, D 2h, D 3h )] were determined. The results indicated that the resistance of E. coli was influenced by the pre-exposure period in the orange juice, with increased resistance to UV-C observed for periods >2 h. Furthermore, the sensitivity of cells to subsequent UV-C treatment was found to be strain-dependent. The results may allow the development of more reliable UV-C radiation processes for orange juice processing aiming the inactivation of pathogenic E. coli . Highlights: Adaptation of 10 E. coli strains in orange juice and increased resistance to UV-C Resistance of E. coli was influenced by pre-incubation period in orange juice (OJ). Cells exposed >2 h in OJ showed increased resistance to UV-C treatment. Sensitivity of cells in OJ and to subsequent UV-C treatment was strain-dependent.